PREVALENCE AND ANTIBIOGRAM OF Salmonella enterica AMONG PATIENTS ATTENDING SELECTED HOSPITALS IN SOKOTO METROPOLIS - GARBA, I.,; UMAR, A. I.,; TIJJANI, M. B.,; ALIYU M. S.,; UMARE, Y.,; RAJI, M. I. O,; UNATA, I. M., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Salmonellaenterica is a rod-shaped, flagellated, facultative anaerobic Gram-negative bacterium and a member of the genus Salmonella, a number of its serovars are serious human pathogens. This study was designed to determine the prevalence of Salmonellaenterica among patients suspected of gastrointestinal tract infections in some selected hospitals within Sokoto metropolis and to determine the antibiogram profile of the organisms isolated. A total of 187 stool samples of male and female patients aged 1-52 years were cultured for the presence of Salmonella species. The prevalence of Salmonella enterica among the patients was 14.4%. A prevalence of 22.0% was found among patients in the age group of 11-15 years, followed by patients in the age group 6-10 with a prevalence of 17.6%. The lowest prevalence 5.9% was observed among patients in the age group 1-5; Patients in the age group16-20 had a prevalence of 16.7% while patients aged had a prevalence of 13.3%. Antibiotic susceptibility test showed that the isolates were sensitive to Gentamicin 37%, Nitrofurantoin 59%, ciprofloxacin 78%, ceftriaxone 41%, ceftazidime 33% and cefuroxime 67%but resistance to Cloxacillin 96%, erythromycin 100%, Ampicillin 100%and Augmentin 100%was observed. Further research to detect presence of salmonellae in clinical samples and its antibiotic susceptibility profile is hereby recommended.